MOBILE WEB IMPLEMENTATION OF DETERMINING PERFORMING EMPLOYEES IN REGENCY HOTELS BY WEIGHTING THE SIMPLE ADDITIVE WEIGHTING METHOD - Verawati, Verawati (Bakti Nusantara Institute, 2023)
Regency Hotel is a hotel located in Gadingrejo sub-district of Pringsewu Regency which has many employees. There are Dozens of Employees who work at Regency Hotels. Regency Hotel Management requires a System to find the best employees who are entitled to get rewards. need a system to determine the best employees. To avoid subjectivity, for this reason a system with accurate and precise calculation methods is needed. Here the author will design a decision support system to determine the best employees at the Regency hotel using the SAW method. The SAW method is a method used for a decision support system based on the required criteria. With this system, the best employee selection at Regency hotels is very precise and accurate without any subjectivity.